Model Kepemimpinan Transformasional dan Kontribusinya terhadap Proses Decision Making dan Peningkatan Kinerja Guru di MA Ar-Ridlo Pekuncen Kabupaten Banyumas - Fatimah Assegaf (Institut Agama Islam Negeri Purwokerto, 2020)
Abstract Leadership is a competency that must be owned by madrasah principals. Decision making in educational organizations is directly related to the head of the madrasah. The principal of the madrasah as manager has an important role in making decisions quickly, precisely and effectively by using data and information for optimal educational environmental performance. Decision-making by the head of the MA Ar - Ridlo Pekuncen Banyumas has gone well, this can be seen from the processes and stages carried out by the head of the madrasah in making decisions with observation, data, planning and recording related to education in madrasahs. Then, conduct deliberations with teachers to take policies, take an interpersonal approach to teachers to hold events, give ideas, involve teachers in training, and supervise as supervisory activities. As stated in the teacher work assessment, this is useful for increasing the potential and performance of teachers, to improve the quality of teaching and learning outcomes at MA Ar - Ridlo Pekuncen Banyumas. Keyword : Principal, Decision-Making, Teachers; Performance, Senior High School